The effect of the introduction of the ERAS protocol in laparoscopic total mesorectal excision for rectal cancer - Huibers, C. J. A. (Springer-Verlag, 2011)
OBJECTIVE: The aim of the study was to determine whether the introduction of the Enhanced Recovery after Surgery (ERAS) protocol in laparoscopic total mesorectal excision (TME) for rectal cancer offers additional advantages concerning postoperative hospital stay compared to laparoscopy and conventional care. METHODS: A consecutive series of patients that underwent a laparoscopic TME for rectal cancer in a single institution between January 2004 and July 2009 were retrospectively included in this study. The ERAS protocol was introduced in this cohort in January 2007. The study cohort was divided in a conventional care group and an ERAS group. Both groups were compared for primary and secondary outcome measures. The primary outcome measure was postoperative length of hospital stay. RESULTS: Seventy-six patients were included: 43 in the ERAS group and 33 in the conventional care (control) group. Median hospital stay was 7 days (range 2–83 days) in the ERAS group and 10 days (range 4–74 days) in the control group (p = 0.04). Return of bowel function occurred on days 2 and 3 respectively (p < 0.001). There were no significant differences between both groups concerning postoperative complications, readmission rate and reoperations. Thirty-day mortality was absent in both groups. CONCLUSION: These results suggest that the introduction of the ERAS protocol in laparoscopic TME leads to a further reduction in length of hospital stay.